Back Cover: Type‐Dependent Identification of DNA Nucleobases by Using Diamondoids (ChemPhysChem 16/2014). Issue 16 (10th November 2014) - Maier, Frank C.; Fyta, Maria
<x xml:space="preserve">Abstract</x> Quantum mechanical calculations were used to study the interaction and electronic properties of different DNA units with tiny diamondoids. On p. 3466 F. C. Maier and M. Fyta describe how the relative orientation of the diamondoid and the DNA units plays a significant role in DNA detection.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>